Overview of over- the- counter practices in the world combined with a study on exploration of vitamin consumption in İstanbul - Borat, Ayşe Işıl (My University, 1998)
unknown
Keywords: Genel yönetim; İlaçlar, Reçetesiz; Pazarlama yönetimi